Big data emerging technology: Insights into innovative environment for online learning resources - Huda M.; Maseleno A.; Atmotiyoso P.; Siregar M.; Ahmad R.; Jasmi K.A.; Muhamad N.H.N.; Mustari M.I.; Basiron B. (Kassel University Press GmbH, 2024)
Indexed by WOS/SCOPUS/ERA